Recent Trends and the Impact of the Affordable Care Act on Emergency Department Visits and Hospitalizations for Gastrointestinal, Pancreatic, and Liver Diseases. Issue 3 (March 2020) - Barakat, Monique T.; Mithal, Aditi; Huang, Robert J.; Sehgal, Alka; Sehgal, Amrita; Singh, Gurkirpal; Banerjee, Subhas
Abstract : Background: The Affordable Care Act (ACA) with Medicaid expansion implemented in 2014, extended health insurance to >20-million previously uninsured individuals. However, it is unclear whether enhanced primary care access with Medicaid expansion decreased emergency department (ED) visits and hospitalizations for gastrointestinal (GI)/pancreatic/liver diseases. Methods: We evaluated trends in GI/pancreatic/liver diagnosis-specific ED/hospital utilization over a 5-year period leading up to Medicaid expansion and a year following expansion, in California (a state that implemented Medicaid expansion) and compare these with Florida (a state that did not). Results: From 2009 to 2013, GI/pancreatic/liver disease ED visits increased by 15.0% in California and 20.2% in Florida and hospitalizations for these conditions decreased by 2.6% in California and increased by 7.9% in Florida. Following Medicaid expansion, a shift from self-pay/uninsured to Medicaid insurance was seen California; in addition, a new decrease in ED visits for nausea/vomiting and GI infections, was evident, without associated change in overall ED/hospital utilization trends. Total hospitalization charges for abdominal pain, nausea/vomiting, constipation, and GI infection diagnoses decreased in California following Medicaid expansion, but increased over the same time-period in Florida. Conclusions: We observed a striking payer shift for GI/pancreatic/liver disease ED visits/hospitalizations after Medicaid expansion in California, indicating a shift in the reimbursement burden in self-pay/uninsured patients, from patients and hospitals to the government. ED visits and hospitalization charges decreased for some primary care-treatable GI diagnoses in California, but not for Florida, suggesting a trend toward lower cost of gastroenterology care, perhaps because of decreased hospital utilization for conditions amenable to outpatient management. Abstract : Supplemental Digital Content is available in the text.